Humanistic Approach to Islamic Education Learning Management in Shaping Religious Maturity Among High School Students: An Exploratory Study - Ahmad Salamuddin; Munawar Rahmat; Mokh. Iman Firmansyah; Edi Suresman (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Research that explicitly explores the relationship between the humanistic approach in Islamic Religious Education and the formation of students' religious maturity remains very limited. This gap highlights the need for further investigation, both theoretically, to understand how humanistic principles relate to adolescent religious development, and practically, to design effective instructional strategies in increasingly pluralistic school environments. Moreover, the application of the humanistic approach in the management of Islamic Religious Education learning, especially at the senior high school level, has not been extensively studied. This study aims to provide an exploratory overview of the management of Islamic Religious Education learning through a humanistic approach in senior high schools. A qualitative method was employed, involving interviews with four teachers across four different schools. The data were analyzed using NVivo version 15. The findings indicate that teachers have applied humanistic-based learning management to foster students' religious maturity, starting from the planning stage to implementation and evaluation. However, several challenges remain, including students' low awareness of worship practices, uneven levels of religious consciousness, and limited supporting facilities. This research recommends strengthening teacher training and institutional support to ensure the optimal implementation of the humanistic approach in PAI learning.